Developmental Links between Teacher-Child Closeness and Disobedience for Boys Placed in Special Education. Issue 4 (2nd October 2018) - Breeman, Linda D.; van Lier, Pol A. C.; Wubbels, Theo; Verhulst, Frank C.; van der Ende, Jan; Maras, Athanasios; Hopman, Juliette A. B.; Tick, Nouchka T.
ABSTRACT: The aim of this study was to examine developmental links between disobedience and teacher-child closeness in a sample of boys with psychiatric disorders (i.e., emotional and behavioral disorders (EBD) and autism spectrum disorders (ASD)) and special educational needs who are placed in special education. More specifically, this study examined whether developmental links were different between boys with EBD ( n = 150) versus boys with ASD ( n = 122). Developmental links between disobedience and teacher-child closeness were investigated by incorporating a multi-informant perspective using teacher, child, and peer ratings and analyzed using autoregressive cross-lagged models across three waves within one school year. Results showed that in general, developmental links between teacher-child closeness and disobedience were stronger for boys with EBD than for boys with ASD. Specifically, boys with EBD experiencing less teacher-child closeness showed more disobedience, which in turn negatively affected their relationship development according to teacher ratings. Surprisingly, for boys with ASD, higher levels of disobedience predicted higher levels of teacher-rated teacher-child closeness during the school year. Our results offer more insight into the differential impact of teacher-child closeness on the behavioral problems for children with EBD and ASD.